2021
DOI: 10.30595/pharmacy.v18i1.9347
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Cassava (Manihot esculenta Crantz) Tuber Extract Gel and Effectiveness Test on Burns in Rabbit (Oryctolagus cuniculus)

Abstract: Burn is heat transfer in which the source can be direct or indirect contact with fire, electricity, friction chemicals or radiation. It can cause damage of skin tissue even in a state of multisystem injury leading to serious disorders. Systemic effects and mortality caused by burn is generally determined by the extent and depth of affected skin. Cassava (Manihot esculenta Crantz) contains carbohydrates, phosphorus, calcium, vitamin C, vitamin B1, protein and iron. Furthermore, substances contained in cassava a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Another study in India managed to isolate silver nanoparticles from Tectona grandis wood flour, reporting comparable results with soframycin treatment on excised wounds in rats 120 . In vitro studies found that cassava extract accelerated burn wound healing in rates 121,122 . Pap is a traditional fermented corn flour from West Africa that was reportedly used as burn first aid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in India managed to isolate silver nanoparticles from Tectona grandis wood flour, reporting comparable results with soframycin treatment on excised wounds in rats 120 . In vitro studies found that cassava extract accelerated burn wound healing in rates 121,122 . Pap is a traditional fermented corn flour from West Africa that was reportedly used as burn first aid.…”
Section: Discussionmentioning
confidence: 99%
“…120 In vitro studies found that cassava extract accelerated burn wound healing in rates. 121,122 Pap is a traditional fermented corn flour from West Africa that was reportedly used as burn first aid. There is no literature studying the use of pap in burns, but the fermentation in pap can lead to wound infection and may worsen the scar.…”
Section: Kitchen Materialsmentioning
confidence: 99%